Anhydrous weight loss kinetics model development for torrefied green waste - Nur Ashikin, Jamin; Noor Asma Fazli, Abdul Samad; Suriyati, Saleh (IOP Publishing Ltd, 2019)
One of the compositions of municipal solid waste (MSW) is green waste (GW) that collected from landscaping, garden, yard and trimming waste. GW has potential in becoming a biomass feedstock, but poses some drawbacks such as high moisture content, low heating value, high O/C and H/C ratios. Implementation of torrefaction as pre-treatment will improve the GW properties. During torrefaction, biomass is decomposed and leads to anhydrous weight loss (AWL). The estimation model for AWL is significant to study thermal degradation of GW. The aim of this work is to study two steps reaction in series for AWL prediction. GW were torrefied under inert condition at 240-300°C, 10°C/min heating rate and 30 minutes holding time using thermogravimetric analysis (TGA). Two steps reaction series model named Di Blasi and Lanzetta with extended non-isothermal phase is used in developing the AWL model. From initial guess, the parameters of activation energy and kinetic constant are adjusted to fit the calculated AWL to experimental AWL data by applying nonlinear optimization 'lsqcurvefit' routine in Matlab. The estimated kinetic parameters been used for AWL model and later being compared to experimental data from TGA. Good agreement obtained between experimental and model data indicating good kinetic parameters estimation.